(untitled) (Experimental biology, 2015)
The methods of approaching the enteral application of enterosorbent (carbonized rice husk), Spirulina and biocomposite (carbonized rice husk+Spirulina) on functional state of microbiocenose of rat intestine were carried out.Experimental results revealed that the application of biocomposite on the basis of carbonized rice husk and Spirulina lead to the early recovery of microbiocenose of rat intestine, as the number of Lactobacteria increased and the number of Enterobacteria decreased.